2007
DOI: 10.1017/s0266462307070286
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle intervention to prevent diabetes in men and women with impaired glucose tolerance is cost-effective

Abstract: Lifestyle intervention directed toward high-risk subjects would be cost-saving for the healthcare payer and highly cost-effective for society as a whole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0
9

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 26 publications
(27 reference statements)
3
74
0
9
Order By: Relevance
“…Some studies have suggested that preventing diabetes, like preventing some other chronic diseases, would increase medical costs in part because of increased life spans. Other studies (9)(10)(11)(12) have found that diabetes prevention would lead to substantial long-term cost savings, despite the extended life expectancy. To assess the cost implications of diabetes prevention, it is crucial to know lifetime medical costs for people with diabetes relative to those of people without diabetes.…”
mentioning
confidence: 99%
“…Some studies have suggested that preventing diabetes, like preventing some other chronic diseases, would increase medical costs in part because of increased life spans. Other studies (9)(10)(11)(12) have found that diabetes prevention would lead to substantial long-term cost savings, despite the extended life expectancy. To assess the cost implications of diabetes prevention, it is crucial to know lifetime medical costs for people with diabetes relative to those of people without diabetes.…”
mentioning
confidence: 99%
“…Modification of lifestyle has shown promise in preventing type 2 diabetes and is cost-effective in high-risk populations (8) …”
Section: Research Design and Methods -People From Four Remotementioning
confidence: 99%
“…However, there is less agreement with respect to the intensive and costly lifestyle intervention of the DPP and DPS [32][33][34]. Although, their results have demonstrated the efficacy of lifestyle modification for diabetes prevention, long-term compliance with these lifestyle changes has proven difficult, however, and the benefits wane with weight regain (Table 2).…”
Section: Translating Diabetes Prevention Trials To the Public Healthmentioning
confidence: 99%
“…The cost-effectiveness of lifestyle interventions has been examined in a number of clinical trials and computer modelling simulations. Although pharmacological interventions have also been shown to prevent diabetes, the cost effectiveness and risk-benefit ratio are less clear [32][33][34][53][54][55][56][57][58][59][60][61][62][63].…”
Section: Cost-effectiveness Of Diabetes Preventionmentioning
confidence: 99%